SCIENTIFIC VIEWS ON THE GENERAL LINGUISTIC STATUS OF THE TERM - Ergashev , Muhammadjon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article examines the general linguistic status of the term, its place within the lexical system of the literary language, and its distinctive features compared to ordinary vocabulary. The key characteristics of terminology — such as systematicity, semantic precision, monosemy, the requirement for definition, and epistemological function — are analyzed from a theoretical perspective. Drawing on the views of Uzbek and international linguists (H. Dadaboyev, E. Wüster, D.S. Lotte, A.V. Superanskaya, S.V. Grinev-Grinevich, and others), the study discusses the boundaries between terms and common lexical units, as well as the processes of determinologization and reterminologization. The findings indicate that terminology constitutes an integral yet distinctive layer of the literary language, governed by specific normative requirements and systemic relations. These properties play a crucial role in ensuring precision and stability in scientific discourse.